Regulation of post-Golgi LH3 trafficking is essential for collagen homeostasis - Blerida Banushi (Nature Portfolio, 2016)
Lysine hydroxylation of procollagen precursors by LH3 is required for collagen fibril crosslinking and stabilization. Here the authors show that the trafficking protein VIPAR is required for correct sorting of LH3 into post-Golgi collagen carriers and for correct collagen modification and structure.